Which positive factors determine the GP satisfaction in clinical practice? A systematic literature review. Issue 1 (December 2016) - Le Floch, B.; Bastiaens, H.; Le Reste, J.; Lingner, H.; Hoffman, R. D.; Czachowski, S.; Assenova, R.; Koskela, T. H.; Klemenc-Ketis, Z.; Nabbe, P.; Sowinska, A.; Montier, T.; et al.
Abstract Background Looking at what makes General Practitioners (GPs) happy in their profession, may be important in increasing the GP workforce in the future. The European General Practice Research Network (EGPRN) created a research team (eight national groups) in order to clarify the factors involved in GP job satisfaction throughout Europe. The first step of this study was a literature review to explore how the satisfaction of GPs had been studied before. The research question was "Which factors are related to GP satisfaction in Clinical Practice?" Methods Systematic literature review according to the PRISMA statement. The databases searched were Pubmed, Embase and Cochrane. All articles were identified, screened and included by two separate research teams, according to inclusion or exclusion criteria. Then, a qualitative appraisal was undertaken. Next, a thematic analysis process was undertaken to capture any issue relevant to the research question. Results The number of records screened was 458. One hundred four were eligible. Finally, 17 articles were included. The data revealed 13 subthemes, which were grouped into three major themes for GP satisfaction. First there were general profession-related themes, applicable to many professions. A second group of issues related specifically to a GP setting. Finally, a third group was related to professional life and personal issues. Conclusions A number of factors leading to GP job satisfaction, exist in literature They should be used by policy makers within Europe to increase the GP workforce. The research team needs to undertake qualitative studies to confirm or enhance those results.